Os percalços e necessidades no caminho do professor iniciante - Diniz, Thaís Mota (2020)
This research aimed to identify the main challenges and difficulties faced by a group of beginning teachers, allocated in the private and public networks of municipalities in the state of São Paulo. In addition, it intended to identify the strategies used by these teachers to respond to adversities in their professional practices, as well as to know their training needs. To compose this work, at first, the researcher training path was outlined, alomg with her concerns as a teacher, which directed her towards this research. In the sequence, accordingly of theorists such as Marcelo García (1999; 2012), Denise Vaillant (2012), Michael Huberman (1995), considerations were developed about the initial path of teachers, discussing aspects related to initial training and the most frequent adversities in their way, working conditions for instance. Then, the concept of training needs was discussed, from the perspective of Estrela, Madureira and Leite (1999) and Esteves and Rodrigues (2006), especially its potential as a starting and ending point for the design of training processes, in order to increase awareness and reflection about the professional practice of teachers, especially at the beginning of their careers. In terms of methodology, the qualitative approach was adopted, due to understand it capable of presenting not only the perspective of subjects, but also the meanings they attribute to their experiences. In order to achieve this aim, a questionnaire was used to collect the characterization and manifestation data on the defined topics (survey of the main challenges, coping strategies and training needs), from thirty participants. The data were organized and submitted to prose analysis (ANDRÉ, 1983). The results showed that the main challenges and difficulties of teachers correspond to working conditions and their implications, such as the devaluation of wages and social recognition, the lack of partnership among peers, management and family, and the lack of adequate resources and training. As strategies, the beginners proved to be adaptive specialists, since they demonstrated that they had sought to solve their doubts in different ways and were concerned with innovating and taking care of the student learning. Concerning the knowledge they consider necessary, three central directions were indicated regarding the researcher teacher, the pedagogical tact and general pedagogical knowledge, of contents, among others. With this in mind it was thought about how the identification and knowledge of the training needs of beginners teachers can contribute to planning training processes, aiming at continuous professional development and a way to mitigate the initial obstacles of teaching. Taking this into account, the relevance of this theme is understood, although it would be possible to recognize there are researches about the beginning of teaching, such studies are still below the complexity that the subject requires